Effect of resveratrol on menstrual cyclicity, hyperandrogenism and metabolic profile in women with PCOS. Issue 6 (June 2021) - Mansour, Asieh; Samadi, Majid; Sanginabadi, Milad; Gerami, Hadis; Karimi, Sara; Hosseini, Saeed; Shirzad, Nooshin; Hekmatdoost, Azita; Mahdavi-Gorabi, Armita; Mohajeri-Tehrani, Mohammad Reza; Qorbani, Mostafa
Summary: Aim: The aim of this randomized trial was to find whether resveratrol could improve menstrual dysfunction, clinical signs (i.e., acne and hair loss), and the biochemical evidence of hyperandrogenism in the women with PCOS. Methods: Women, in the age range of 18–40 years, diagnosed with PCOS, as defined by the Rotterdam criteria, and no other known cause of abnormal menstruation, were recruited. Participants were randomized based on a 1:1 ratio, to either 1000 mg resveratrol or 1000 mg placebo daily groups, for a period of 3 months. Results: Seventy-eight patients were randomized: 39 to the resveratrol group and 39 to placebo. Results were analyzed according to the intention-to-treat principle. At the end of study, it was found that women who received resveratrol had a statistically higher regular menstruation rate, as compared to those who got placebo (76.47% vs. 51.61%; p = 0.03), and lower hair loss (32.10% vs. 68.00%; p = 0.009). We also found no significant differences between the two groups in terms of ovarian and adrenal androgens, sex hormone binding globulin (SHBG) levels, free androgen index (FAI), glycoinsulinemic metabolism and lipid profile. Moreover, the resveratrol treatment did not interfere with the thyroid, liver and kidney functions. The negative effect of resveratrol on the body composition was also observed, though not influencing changes in the weight, relative to the placebo group. Conclusion: Resveratrol improved menstrual cyclicity and hair loss, even though levels of androgens, insulin and lipids remained unchanged.